2013
DOI: 10.1007/s13730-013-0089-7
|View full text |Cite
|
Sign up to set email alerts
|

Prerenal uremia induced by severe diarrhea due to colon adenoma: a case of McKittrick–Wheelock syndrome in an elderly patient

Abstract: McKittrick-Wheelock syndrome can be successfully treated by emergent dialysis, prescription of bicarbonate, and endoscopic submucosal dissection, which allow elderly people suffering from this syndrome to maintain their activities of daily living. In patients with this syndrome, a large colonic villous adenoma secretes excessive amounts of mucus and causes severe electrolyte depletion and dehydration. An 81-year-old man who had been suffering from chronic renal failure (creatinine 256.4 lmol/L), hypertension, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Our literature review revealed three cases of similar lesions treated through ESD, all of which were performed in Japanese centers. However, to our knowledge, this is the first report of such a rectal adenoma manifesting with MKWS treated through ESD outside of Japan [6,39,40]. From the three previously reported cases, one tumor was resected in a single procedure, like in our case, while the other two required two and three subsequent procedures, respectively, to achieve a complete resection.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 54%
“…Our literature review revealed three cases of similar lesions treated through ESD, all of which were performed in Japanese centers. However, to our knowledge, this is the first report of such a rectal adenoma manifesting with MKWS treated through ESD outside of Japan [6,39,40]. From the three previously reported cases, one tumor was resected in a single procedure, like in our case, while the other two required two and three subsequent procedures, respectively, to achieve a complete resection.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 54%
“…The decrease in volume also culminates in secondary hyperaldosteronism, increasing alkalosis and hypokalemia. 3,16 Therefore, associated with dehydration and mucous diarrhea, the main findings are hyponatremia and hypokalemia. The first encompasses symptoms such as headache, nausea, lethargy, muscle cramps, weakness and seizures.…”
Section: 192428mentioning
confidence: 99%